Amleth’s Vengeance In Sjón & Robert Eggers’ The Northman Movie Script (2020) - Muhammad Ilham Rahmansyah; Cahyaningsih Pujimahanani; Hariyono (PT. Padang Tekno Corp, 2026)
The purpose of this article is to find out how Amleth's vengeance is portrayed in Sjón & Robert Eggers' The Northman movie script. This movie script illustrates how the theme of vengeance is portrayed through the main character, Amleth. The thesis writer uses a qualitative research method that allows for research based on the indicators of vengeance, such as its causes, characteristics, and effects. The characteristics are Retribution, Harm for Harm, Personal Motive. And the causes of this vengeance are anger, humiliation, betrayal, and grief. It is seen that Amleth's vengeance is portrayed through his character transformation from a playful child into a brutal warrior full of hate. The pursuit of vengeance within this film is represented as an inescapable fate that leads the main character to his death. The condition of vengeance is a central theme by portraying Amleth's quest and its effects on himself, his mother, his uncle, his cousin, and his lover through his actions and dialogue